MEASUREMENT OF SERUM TESTOSTERONE IN KACANG GOAT BYUSING ENZYME-LINKED IMMUNOSORBENT ASSAY (ELISA) TECHNIQUE: THE IMPORTANCE OF KIT VALIDATION (Pengukuran Testosteron Serum Kambing Kacang dengan Teknik Enzyme-Linked Immunosorbent Assay (ELISA): Pentingnya Validasi Kit) - Gholib G; Sri Wahyuni; Okta Hilda Kadar; Mulyadi Adam; Triva Murtina Lubis; Azhar A; Muslim Akmal; Tongku Nizwan Siregar; Teuku Armansyah; Taufiq Purna Nugraha (Jurnal Kedokteran Hewan, 2016)
This study was conducted to validate a commercial testosterone enzyme-linked immunosorbent assay (ELISA) kits (DRG EIA-1559) inanalytic and biological manner for measuring serum testosterone concentrations in kacang goats. This study used 18 healthy kacang goats, six bucks (2 years), six kids (6 months), and six does (2 years). Blood samples were collected from jugular vein and prepared as serum. Two validation tests were performed, an analytical validation comprises a parallelism, accuracy, precision and sensitivity and a biological validation by comparing testosterone concentration from bucks, kids, and does. Testosterone concentrations were measured using ELISA technique. Data of analytical validation were analyzed descriptively and test of equality of slope was performed to see the parallelism between samples and standard curves. Analysis of variance (ANOVA) was used for biological validation data. Results of parallelism showed that sample curve was parallel to the standard curve. Accuracy, precision (% CV of intra-and inter-assay) and sensitivity of the assay were 99.65±4.27%, 10%, 15% and 0.083 ng/ml, respectively. Results of biological validation showed that the assay used were accurately measured testosterone which testosterone concentrations in bucks were significantly higher compared to kids and does (P0.05). In conclusion, a commercial testosterone ELISA kits (DRG EIA-1559) is a reliable assay for measuring serum testosterone concentration in kacang goats. Key words: analytical and biological validations, ELISA, testosterone, kacang goat